Plasmonic interferences of two-particle N00N states. (21st May 2018) - Vest, Benjamin; Shlesinger, Ilan; Dheur, Marie-Christine; Devaux, Éloïse; Greffet, Jean-Jacques; Messin, Gaétan; Marquier, François
Abstract: Quantum plasmonics lies at the intersection between nanophotonics and quantum optics. Genuine quantum effects can be observed with non-classical states such as Fock states and with entangled states. A N00N state combines both aspects: it is a quantum superposition state of a Fock state with N excitations in two spatial modes. Here we report the first observation of two-plasmon ( N = 2) N00N state interferences using a plasmonic beamsplitter etched on a planar interface between gold and air. We analyze in detail the role of losses at the beamsplitter and during the propagation along the metal/air interface. While the intrinsic losses of the beamsplitter are responsible for the emergence of quantum nonlinear absorption, we note that N00N states decay N times faster than classical states due to propagation losses.